Technical mitigation measures to reduce the bycatch of sharks: there is no silver bullet - David A. D. Drynan; G. Barry Baker; Stephen T. Garnett; Peter M. Kyne (Reviews in Fish Biology and Fisheries, 2026)
Incidental catch (bycatch) of sharks in commercial fisheries is driving global population declines. In this review we assess the efficacy of a comprehensive list of technical bycatch mitigation measures for all major commercial fishing gears. We structured our review around the three stages of capture where opportunities exist to mitigate bycatch: preventing capture; increasing escape probability; and decreasing at-vessel/post-release mortality. Adding magnetic repellents in static gears, removing lightsticks from longlines, adding artificial lights in gillnets, optimising gillnet mesh size, and using non-entangling Fish Aggregating Devices are all effective (i.e., reduce bycatch mortality) without causing harm (i.e., increase in shark catch, or injuring sharks or other species) or reducing target catch, and were feasible to implement. To enable escape, the use of excluders with appropriately configured escape panels/hatches in trawls is effective and feasible. The use of nylon leaders in place of wire in longlines is also effective and feasible but can harm sharks. Post-release mortality decreases by cutting leaders at the hook. Use of circle hooks in longlines is effective at reducing bycatch mortality, but can increase catch rates of sharks. Overall, we found that few measures were supported by studies that reported empirical data. Of those that are effective, many are unlikely to be adopted by fishers because they can reduce target catch, have deleterious impacts on sharks or other species or still require significant investment to resolve technical issues. The variety of measures available and the high degree of interspecific and geographical variation in responses highlights the need for more trials under local conditions before deployment. Future research priorities should include development and incorporation of necromones into commercially viable artificial baits, production of active electrical repellents at scale to encourage uptake, investigating the impact of removal of lightsticks from longlines on shark catch rates, and refinement of circle hook design to reduce shark catch rates.